Creative Music Olah Ulah | Tabuh Kreasi Olah Ulahh” - I Ngurah Edy Upadana (GHURNITA: Jurnal Seni Karawitan, 2024)
Tabuh Creation Olah Ulah is a musical composition inspired by the concept of tri guna, three essential human natures: animals, rajas, and tamas, which are different from each other. Satwam is calm, honest, kind, and wise. Rajas's nature is arrogant and haughty, while Tamas's is lazy and greedy. The three fundamental properties are interrelated and cannot be separated from each other. The concept is poured through the media, revealing Gamelan Semara Dhana, a new Gamelan barungan in the Karawitan of Bali. The method of creation used refers to the book "Panca Sthiti Ngawi Sani" by I Wayan Dibia. In this book, five stages are mentioned, namely the Inspiration Stage (Ngawirasa), the Exploration Stage (Ngewacak), the Conception Stage (Ngerencana), the Execution Stage (Ngewangun), and Ngebah. The form and structure of the work "Olah Ulah" are based on the concept of Tri Angga, which is pengawit, Pengawak, and Pengecet. Pengawit describes the nature of Sattwam: wise, honest, and calm. Pengawak describes the nature of rajas and tamas: arrogant, haughty, and lazy. Pengecet describes neutralizing these three properties so that balance is a Sattwam trait.